Caracterización de los desechos químicos para la elaboración de una propuesta de manejo en la empresa aglomerados Cotopaxi. sector Lasso. provincia Cotopaxi. periódo 2013 - Gómez Calvopiña, Ana Luciola (2013)
In the present research it characterized the chemical waste generated in Cotopaxi Aglomerados located in Lasso Neighborhood, Cotopaxi Province industry for the development of a management proposal. The characterization was performed in the study area was investigated through direct observation. It was determined that chemical waste is generated type : oils, industrial sludge , oil sludge and chemical containers and hydrocarbon phases that have as starting point when using materials input, followed by segregation , internal transport , storage and treatment of chemical waste, which are usually performed by operations staff of each areas where the wastes are generated . It is possible to know the status of each one of production and maintenance of the company where the waste is produced thus achieving information basis for quantitative and qualitative characterization which identifies the quantities and characteristics of waste generated in those areas . It establishes procedures, processes and activities for the comprehensive management of chemical waste in compliance with current regulations. This will lead to improve the safety of all staff of the company, while respecting the environment....